Analysis of the Effcacy and Safety of Amivantamab in Non-small Cell Lung Cancer Patients with EGFR/MET Gene Abnormalities: A Single Center’s Experience - Jingjing WANG; Yujia CHI; Hanxiao CHEN; Bo JIA; Xiaoyu ZHAI; Menglei MA; Jianjie LI; Minglei ZHUO (Chinese Journal of Lung Cancer, 2022)
Background and objective Epidermal growth factor receptor (EGFR) and cellular-mesenchymal to epithelial transition factor (c-Met) are widely expressed on cancer cells. There is a synergistic effect of EGFR and HGF/c-Met pathways on proliferation, downstream activation of signal transduction and an additive effect. Studies show that combination of both signaling pathways could potentially be targeted in a synergistic fashion. Amivantamab, a bispecific monoclonal antibody targeting EGFR and c-Met, yielded robust and durable responses in a variety of clinicals trials. However, few researches have reported its efficacy in Chinese non-small cell lung cancer (NSCLC) patients. This study was conducted to evaluate the effectiveness and tolerance of Amivantamab in NSCLC patients with EGFR/MET gene abnormalities at Peking University Cancer Hospital. Methods The study enrolled NSCLC patients who received Amivantamab in our hospital between August 2020 and December 2021, and analyzed the response, survival, and treatment-related adverse events. Results Fifteen patients were enrolled in this research, and six of them received Amivantamab treatment and the other nine patients received Amivantamab plus Lazertinib treatment. The rates of partial response (PR), stable disease (SD), and progressive disease (PD) were 46.7% (7/15), 46.7% (7/15) and 6.7% (1/15), respectively. The overall response rate (ORR) and disease control rate (DCR) were 28.6% (2/7) and 100.0% (7/7) in seven patients with EGFR exon 20 insertion, respectively. The ORR and DCR were 40.0% (2/5) and 100.0% (5/5) in five post-osimertinib EGFR-mutant patients, respectively. After a median follow-up of 8.7 months, the median progression-free survival and overall survival were not reached. The most common treatment-related adverse events were rash (86.7%), paronychia (80.0%), and infusion-related reactions (60.0%), and most of them were graded as 1 to 2. Grade 3 to 4 adverse events included rash (33.3%), alanine aminotransferase elevation (13.3%), gamma-glutamyl transpeptidase elevation (13.3%), peripheral edema (6.7%), thromboembolism (6.7%), interstitial lung disease (6.7%), and thrombocytopenia (6.7%). Conclusion Amivantamab was effective in Chinese NSCLC patients with EGFR exon 20 insertion and post-Osimertinib EGFR-mutant patients, similar to the results of clinical trials conducted in western countries. Amivantamab was well tolerated and emphases should be put on adverse events such as rash, paronychia, and infusion-related reactions.